Conceptualizing creative school leadership through generativity theory towards school effectiveness - Arivayagan, Keetanjaly; Lope Pihie, Zaidatol Akmaliah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Recently research in creative leadership has ballooned to encompass the essential qualities in organizational leaders (Petrie, 2014). According to Thomson (2011) creative leaders are the mixture of people who able to create and manage the organizational culture and maintain school innovation and effectiveness. Turnbull (2012) explained that creative leaders inspire and encourage feedback by demonstrating through their nourishment behaviour by not being castigated. In this paper, Generativity Theory will be utilized to explore the concept of creativity in leaders. Epstein (1999) presented four main core skills and abilities that assist people in expressing creativity individually which are capturing, challenging, broadening and surrounding. Model of high performing school by Shannon and Bylsma (2007) will be utilized to measure school effectiveness. Consequently, it will be shown through this paper that there is a growing demand on the educational institutions especially school administrator to apply the creative leadership attributes as the 21st century skills in directing schools towards effective school. This paper is meant to provide a better understanding of creative leadership practices in extending the existing knowledge with focus in Epstein, Kaminaka, Phan, & Uda (2013) model of creativity in leaders towards Shannon & Bylsma (2007) model of school effectiveness.